Aesthetic Clinic and Beauty Myths in Indonesia: Discourse Analysis of Beauty Representation in Instagram Accounts - Refti Handini Listyani; Anggaunita Kiranantika; Diah Ariani Arimbi; Emy Susanti (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This study analyzed beauty myths on Instagram accounts of three aesthetic clinics in Indonesia using Sara Mills' critical discourse analysis. Results showed that First, the women were characterized as an object and became the victims, and beauty standards were reconstructed and reproduced by the subjects, namely the Instagram accounts of @dermaster_id, @ertosbeautyclinic, and @natashaskincare aesthetic clinics. Women objectification could not be separated from the existing beauty myth. Second, there were two categories of beauty representations formed in the three Instagram accounts, namely men's beauty representation that consisted of smooth faces, young looks, and firm jaws, and women's beauty representations that consisted of thin cheeks, firm jaw, firm skin, smooth, acne-free, attractive skin, glass skin, and slim, and halal beauty. The study is expected to enrich the repertoire of social science, especially sociology, and develop research on the sociology of the body, feminism study, and the sociology of gender and media.